Nonlinear problems of heat radiating body with thermal thin cover - Berezovsky, A.A.; Komarov, G.N.; Nartova, O.G. (Нелинейные граничные задачи, 1999)
We consider a boundary initial problem for heat conductivity with nonlinear boundary condition, which contains time derivative and tangential part of Laplace operator. Existence and uniqueness theorems for positive solutions of mentioned problems are proved.